Peran identitas nasional dalam membangun jati diri bangsa - Hawa, Rika Ismatul (Maliki Interdisciplinary Journal, 2025)
The identity of a nation is the main foundation in shaping character and the continuity of a country. In Indonesia, known for its cultural, ethnic, and religious diversity, national identity serves as a social glue that maintains the integrity of the nation. However, challenges from globalization and technological developments have had a significant impact on the way young generations think, which may erode local values and trigger a crisis of identity. This article discusses the importance of strengthening national identity through various strategic approaches, such as formal and non-formal education, the role of the family, contributions from mass media, and government policies. With education based on national values, media content supporting cultural preservation, and active family involvement in instilling positive values, it is hoped that national identity can remain strong in facing the challenges of the times. Cooperation among societal elements is key to preserving and enhancing national identity.